Liquidity risk premium and asset pricing in US water transportation - Panayides, Photis; Lambertides, Neophytos; Cullinane, Kevin P B (My University, 2013)
The water transportation of freight has been one of the most important sectors in facilitating international trade and contributing to the growth of the world economy. Bearing in mind the importance of the relation between asset returns and liquidity in water transportation, this paper examines this relation within the context of US traded international water freight transportation firms. Using a Fama-MacBeth analysis, it is shown that the illiquidity risk premium is priced in the water transportation sector beyond the Fama and French and market-wide illiquidity risk factors, indicating higher average returns for stocks with greater illiquidity measures. It is also shown that the market-wide illiquidity factor and the Fama-French SMB and HML risk factors are significant in explaining stock returns. In contrast, market risk is found not to be priced in the water transportation sector. The results are also robust to asset pricing tests over two alternative sub-periods.
Keywords: Aasset pricing; Fama-macbeth analysis; Liquidity risk; Market risk; Water transportation